Rancang Bangun Wedding Organizer Menggunakan Metode Pendekatan User Centered Design - Muhamad Ariandi; Muhammad Ikbal Ernanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Marriage is a sacred thing and when the newlyweds wait for it, a new family will be formed. To carry out these activities, a wedding reception is needed as a form of happiness. In this case, sometimes the bride and groom experience problems in managing their wedding reception, due to lack of information and limited time. Seeing from this phenomenon, one of the wedding organizers or who is familiar with wedding organizers (WO) took the initiative to expand their business to be wider. One of the wedding organizers is the Baba Family. Where the current system used by the Baba wedding organizer family is still using a manual system, the process must come directly to the place. Of course, this is one of the obstacles for the Baba Wedding Organizer family to share information and existing processes, because it cannot be done by businesses all the time. From this, the Baba Family, in overcoming their business problems, built an information system for ordering wedding organizers. The purpose of the research is to build a wedding organizer system in searching for information on wedding services consisting of wedding package prices, aisle and dress simulations, buildings, catering, and online guest books. By building the information system, it is necessary to do an approach method so that it is better and measurable. One approach method is using the User Centered Design (UCD) approach, a method in a design design that focuses on user needs. In relation to Information Systems, User Centered Design is part of the SDLC (System Development Life Cycle), so that application designs developed through UCD will be optimized and focused on end-user needs. The information system built by the researcher is able to provide future business value for the Baba Family on their wedding organizer. So that the system used can provide the right information and according to the needs of its users, as well as the transaction process for ordering wedding organizers to be easier and more helpful.